Community intervention improves knowledge of HIV status of adolescents in Zambia: findings from HPTN 071-PopART for youth study - Shanaube, Kwame (AIDS, 2017)
OBJECTIVE: To determine the uptake of home-based HIV counselling and testing (HCT) in four communities of the HPTN 071 (PopART) trial in Zambia among adolescents aged 15–19 years and explore factors associated with HCT uptake. DESIGN: The PopART for youth study is a three-arm community-randomized trial in 12 communities in Zambia and nine communities in South Africa which aims to evaluate the acceptability and uptake of a HIV prevention package, including universal HIV testing and treatment, among young people. The study is nested within the HPTN 071 (PopART) trial. METHODS: Using a door-to-door approach that includes systematically revisiting households, all adolescents enumerated were offered participation in the intervention and verbal consent was obtained. Data were analysed from October 2015 to September 2016. RESULTS: Among 15 456 enumerated adolescents, 11 175 (72.3%) accepted the intervention. HCT uptake was 80.6% (8707/10 809) and was similar by sex. Adolescents that knew their HIV-positive status increased almost three-fold, from 75 to 210. Following visits from community HIV care providers, knowledge of HIV status increased from 27.6% (3007/10 884) to 88.5% (9636/10 884). HCT uptake was associated with community, age, duration since previous HIV test; other household members accepting HCT, having an HIV-positive household member, circumcision, and being symptomatic for STIs. CONCLUSION: Through a home-based approach of offering a combination HIV prevention package, the proportion of adolescents who knew their HIV status increased from ∼28 to 89% among those that accepted the intervention. Delivering a community-level door-to-door combination, HIV prevention package is acceptable to many adolescents and can be effective if done in combination with targeted testing.